INOVASI PEMBELAJARAN SEKOLAH DI KALIMANTAN TIMUR PADA ERA REVOLUSI INDUSTRI 4.0 - Dina, Dina Destari; Erna (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
Instructional inovations in schools are phenomena that adjust to new teaching and learning style based on the current situation and condition to fulfill the demand of industrial revolution 4.0 era. This research was aimed at knowing the innovation that could improve the students’ competence in East Kalimantan, knowing in what way blended learning influenced the improvement of students’ competence in East Kalimantan, and knowing the planning of good blended learning program in the industrial era 4.0 from 2020 up to 2035. The research method used was qualitative descriptive. The results showed that in the teaching and learning, the teachers implemented blended learning as their innovation by combining face-to-face and online learning. Blended learning enabled students to study individually or in group at the time, so it was so effective and efficient. The planning of successful blended learning program for the coming years must have been set up carefully, particularly in determining the kinds and content of the materials, facilities, and human resources since the success of blended learning lied on the model of Learning Management System that was developed and implemented